A Triangulated Study of Workplace English Needs of Electrical Engineering Students - Samira kazempourian; Abbas Ali Rezaee (Journal of Modern Research in English Language Studies)
English for Specific Purposes (ESP) is one of the considerable programs in the world of English language teaching and research since it pertains to specific needs of various specialties. Meanwhile, university students’ ability to communicate effectively through English language can greatly affect their career development in the target situation, namely in their future workplace. Moreover, ESP instructors play a conspicuous role in flourishing students’ English achievements, as they need to be equipped with the knowledge and awareness of their students’ English needs not only in the academic setting but also in the workplace environment. Thus, this study intended to investigate workplace English needs of Electrical Engineering (EE) students from ESP instructors’ point of view, together with the English requirements of EE employers in different Electrical companies in Iran. In doing so, data were elicited from 97 EE students, 39 EE employers from 15 well-reputed Electrical companies, and 15 ESP instructors. The results of t-test between instructors and employers indicated that ESP instructors were not fully aware of EE students’ future workplace needs. Therefore, having the rudimentary knowledge of the technical content in English on the part of ESP instructors can raise their awareness toward EE workplace needs Moreover, the findings of interview revealed that EE employers required their prospective workforce to be more proficient in speaking skills and to be more skilled in technical translation. The findings provide implications for ESP instructors and curriculum developers in order to be more aware of English needs of EE workforce.